A 48-Year-Old Man with Reducible Right Scrotal Hernia: A Case Report - Oriza Varera; Saut Idoan Sijabat (Green Publisher Indonesia, 2025)
A scrotal hernia is a continuation of an inguinal hernia that enters the scrotum. The prevalence of this case is most common in developing countries at 67% compared to developed countries of around 6%. Risk factors that trigger this disease are age, occupation, gender, congenital and previous surgery history. In this case, it was reported that a 48-year-old male patient came with complaints of a lump in the right testicle since 10 years ago. The lump will appear and enlarge especially when the patient coughs, strains or does heavy activities. The lump will disappear and re-enter if the patient lies down and rests. There is no history of trauma and other complaints in the patient. In the examination of the localized status of the dextra scrotum, it was found that there was a round mass or lump with a size of 7x5x3 cm, a dense elastic consistency, the same color as the skin, firmly bounded, intestinal noise (+), inflammatory signs (-), and a lump could be inserted into the abdominal cavity. The operative therapies performed for hernia cases are hernioraphy and hernioplasty.